2017
DOI: 10.1080/10826084.2017.1285315
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behaviors Among Adolescents in Foster Care: A Gender-Based Analysis

Abstract: Background and Objectives Adolescents in foster care are at high risk for cigarette smoking. However, it is not clear how their smoking behaviors vary by gender. The present study examined lifetime and current smoking among males and females, and explored gender-specific risk factors for engagement in smoking behaviors. Method Data from the Multi Site Evaluation of Foster Youth Programs was used to evaluate patterns of smoking among adolescents aged 12–18 years (N=1,121; 489 males, 632 females). Results Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…Although gender of CL user was not associated to the level of knowledge and practice of CL usage in our study, one should note that 92% of the CL users in our study as well as 77% were female in a study in Pakistan 4 . Imparting knowledge and demonstrate preferred CL usage should be gender specific in Saudi Arabia for better practices 14 …”
Section: Discussioncontrasting
confidence: 60%
“…Although gender of CL user was not associated to the level of knowledge and practice of CL usage in our study, one should note that 92% of the CL users in our study as well as 77% were female in a study in Pakistan 4 . Imparting knowledge and demonstrate preferred CL usage should be gender specific in Saudi Arabia for better practices 14 …”
Section: Discussioncontrasting
confidence: 60%
“…According to a 2016 study [1], 29.8% of at-risk adolescents were exposed to smoking as compared with 1.7% of non-at-risk adolescents, thus, showing about 15 times higher risk of smoking. In addition, another study reported that the risk of smoking was high among both male and female adolescents who had runaway experience [24]. According to one survey that examined the differences, in terms of smoking behaviors, among adolescents who received foster care, both male and female adolescents started smoking at similar ages and showed similar rates of lifetime and current smoking [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study reported that the risk of smoking was high among both male and female adolescents who had runaway experience [24]. According to one survey that examined the differences, in terms of smoking behaviors, among adolescents who received foster care, both male and female adolescents started smoking at similar ages and showed similar rates of lifetime and current smoking [24]. However, it also reported that smoking experiences were more common among victims of sexual abuse and female victims of non-sexual abuse; this tendency resulted in significant differences, in terms of sex-related factors, between risk factors associated with smoking among male and female adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the general youth population of Canada and the US find that household stability, uncrowded housing conditions, no experience in foster care, and higher parental education are associated with less youth smoking (Karlsen et al, 1998;LeMaster et al, 2002;Saewyc et al, 2006;Shpiegel et al, 2017;Simons-Morton & Farhat, 2010;Soteriades & DiFranza, 2003;Wen et al, 2009). Data from the RHS also show that low family socioeconomic status is a risk factor for both youth and adult smoking (FNIGC, 2016b).…”
Section: Socioeconomic Statusmentioning
confidence: 99%